Proteoglycan-4 is correlated with longer survival in HCC patients and enhances sorafenib and regorafenib effectiveness via CD44 in vitro - Dituri, Francesco; Scialpi, Rosanna; Schmidt, Tannin A.; Frusciante, Martina; Mancarella, Serena; Lupo, Luigi Giovanni; Villa, Erica; Giannelli, Gianluigi (Cell death & disease, 2020)
Sorafenib and regorafenib administration is among the preferential approaches to treat hepatocellular carcinoma (HCC), but does not provide satisfactory benefits. Intensive crosstalk occurring between cancer cells and other multiple non-cancerous cell subsets present in the surrounding microenvironment is assumed to affect tumor progression. This interplay is mediated by a number of soluble and structural extracellular matrix (ECM) proteins enriching the stromal milieu. Here we assess the HCC tumor expression of the ECM protein proteoglycan 4 (PRG4) and its potential pharmacologic activity either alone, or in combination with sorafenib and regorafenib. PRG4 mRNA levels resulted strongly correlated with increased survival rate of HCC patients ( p = 0.000) in a prospective study involving 78 HCC subjects. We next showed that transforming growth factor beta stimulates PRG4 expression and secretion by primary human HCC cancer-associated fibroblasts, non-invasive HCC cell lines, and ex vivo specimens. By functional tests we found that recombinant human PRG4 (rhPRG4) impairs HCC cell migration. More importantly, the treatment of HCC cells expressing CD44 (the main PRG4 receptor) with rhPRG4 dramatically enhances the growth-limiting capacity of sorafenib and regorafenib, whereas not significantly affecting cell proliferation per se. Conversely, rhPRG4 only poorly potentiates drug effectiveness on low CD44-expressing or stably CD44-silenced HCC cells. Overall, these data suggest that the physiologically-produced compound PRG4 may function as a novel tumor-suppressive agent by strengthening sorafenib and regorafenib effects in the treatment of HCC.